AB0448 Patient-reported outcomes following discontinuation of methotrexate in patients with rheumatoid arthritis treated with subcutaneous tocilizumab: results from a randomised controlled trial. (12th June 2018) - Kremer, J.; Rigby, W.; Singer, N.; Birchwood, C.; Gill, D.; Reiss, W.; Best, J.; Pei, J.; Michalska, M.
Abstract : Background: Patients with rheumatoid arthritis (RA) often receive methotrexate (MTX) in combination with biologics; however, MTX may be discontinued due to intolerance or to reduce the medication burden once disease control is achieved. Whereas previous studies have established the efficacy of tocilizumab (TCZ) initiated as monotherapy (MONO) for the treatment of RA, 1, 2 patient-reported outcomes (PROs) after MTX withdrawal in patients achieving good clinical response to TCZ +MTX have not been evaluated. PROs are important measures when determining response to therapy in patients with RA with respect to health-related quality of life (HRQOL). 3, 4 Objectives: This study evaluated PROs between patients with RA who achieved low disease activity with TCZ +MTX and then continued or discontinued MTX in the COMP-ACT trial (NCT01855789 ). Methods: US patients with RA who were inadequate responders to MTX were enrolled; initial combination therapy included MTX (≥15 mg/week orally) plus TCZ 162 mg subcutaneous either weekly (qw) or every 2 weeks (q2w). Patients who achieved DAS28-ESR≤3.2 at Week 24 were randomised 1:1 to receive TCZ-MONO or continue TCZ +MTX until week 52 (double-blind). Changes in PRO scores were measured between Week 24 and Weeks 40 and 52, and included patient global assessment of disease activity (PtGA; visual analogue score [VAS], 0–100 mm), pain (VAS), Health Assessment Questionnaire Disability Index (HAQ-DI, 0–3) and Functional Assessment of Chronic Illness Therapy (FACIT)-Fatigue. Results: Of the 296 randomised patients (TCZ +MTX, n=148; TCZ-MONO, n=148), 74.8% were women, mean age was 55.5 years, mean RA duration was 6.8 years and mean DAS28-ESR was 6.3 at baseline. At Week 24 (randomization), PRO scores were similar between the randomised treatment groups. The mean changes in PtGA, pain, HAQ-DI and FACIT-fatigue scores from Week 24 to Weeks 40 were similar between the TCZ +MTX and TCZ-MONO groups (table 1). The proportion of patients with HAQ-DI <0.5 was similar between the groups at Week 24 (randomization), and remained similar at Weeks 40 and 52. Conclusions: Patients receiving TCZ who discontinue MTX appear to have similar PROs across multiple measures compared with patients continuing TCZ +MTX. Differences observed in clinical parameters between TCZ-MONO and TCZ +MTX did not appear to achieve a threshold that would be considered clinically meaningful. Similarities in PROs on both treatments were consistent with the clinical efficacy measures previously reported from COMP-ACT. References: [1] Jones G, et al. J Rheumatol2017;44(2):142–6. [2] Dougados M, et al. Ann Rheum Dis. 2013;72(1):43–50. [3] Deshpande PR, et al. Perspect Clin Res. 2011;2(4):137–44. [4] Her M, Kavanaugh A. Curr Opin Rheumatol. 2012;24(3):327–34. Acknowledgements: This study was funded by Genentech, Inc. Disclosure of Interest: J. Kremer Shareholder of: Corrona, LLC, Consultant for: Abbvie, Amgen, Bristol-Myers Squibb, Eli Lilly and Company, Genentech, GlaxoSmithKline, Pfizer, Regeneron and Sanofi, W. Rigby Consultant for: Roche/Genentech, N. Singer Grant/research support from: Merck/EMD Serono (in kind lab resources) and unrestricted educational grants from several companies to MetroHealth for 2016 Cleveland Society of Rheumatology, C. Birchwood Employee of: Genentech, Inc., D. Gill Employee of: Genentech, Inc., W. Reiss Employee of: Genentech, Inc., J. Best Employee of: Genentech, Inc., J. Pei Employee of: Genentech, Inc., M. Michalska Employee of: Genentech, Inc.